PENGARUH BRAND IMAGE, PRODUCT KNOWLEDGE DAN CONSUMER PERCEPTION TERHADAP PURCHASE INTENTION LEMARI ES MEREK SHARP DI KECAMATAN MENGANTI-GRESIK - Suparlan Suparlan (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2014)
With the knowledge of quality brand with a refrigerator and then the man will get to choose where the refrigerator was in accordance with her wishes. Fridge was a household electrical appliance that uses refrigeration (cooling process) to help food preservation. The purpose of this study was to analyze the influence of partial and simultaneous Brand image, Consumer Product Knowledge and Perception to purchase intention in the District of Sharp refrigerator Menganti Gresik. Some of the variables as indicators of Brand image, Consumer Product Knowledge and Perception among other brands, the price benefits, quality, efficient, model, pengoprasian, sales price affect the Purchase Intention in Menganti Gresik district. The analysis tools was to use multiple linear regression with the help of SPSS/Windows.V.15. hypothesis testing used t test and F test, both at a significant level of 5%. Calculation results showed that the three variables were included in the analysis together had a significant effect on Purchase Intention in Menganti Gresik district. This conclusion was based on results that showed the value of F perhitunggan count of 5.787 over 2.699 F table of the three variables, it appeared Consumer Perception had a significant influence calculated t value of 2.489 with a significance level of 0.025%. Based on the results of the analysis was the Purchase Intention in the district of Gresik Menganti very dominant towards Consumer Perception, Consumer Perception of the three variables should be further enhanced so that consumers understand more Brand image, Consumer Product Knowledge and Perception of Purchase intention.